PEMANFAATAN TOTAL BENCHMARKING DALAM PENGUJIAN KEPATUHAN WAJIB PAJAK (STUDI KASUS PADA SEKTOR MANUFAKTUR DI BURSA EFEK INDONESIA) - Gusti Ayu Mahanavami; Wayan Arya Paramarta (Forum Manajemen STIMI Handayani Denpasar, 2015)
Tax revenue is still the largest component and the main source ofdomestic revenue to support financing of government operations and development.Benchmarking conducted by the Directorate General of Taxes arranged in aconcept called Total Benchmarking. This study aimed to analyze the level of taxcompliance assessment using the ratio of total Benchmarking in the manufacturingsector in the Indonesia Stock Exchange and to analyze the results of comparisons of financial ratios taxpayer to total ratio benchmarking. The method used is descriptive qualitative analysis method. Data was collected by interview and documentation.The final conclusion is that during the years 2009-2011, ratios of sample firms arestill many who are under the benchmark tax, except for one company that has a ratioof Gross Profit Margin (GPM), Operating Profit Margin (OPM), pretax profit margin(PPM ), Corporate tax to Turn Over ratio (CTTOR), Net Profit Margin (NPM) abovethe benchmark tax namely PT Holcim Indonesia Tbk (SMCB), although for nontradeincome ratio to sales (pl) in 2010 is negative. Suggestions can be taken intoconsideration for companies who value ratio-the ratio is below the benchmark tax isto revise the SPT and the companies using all available ratios and per item directlydiscuss each part of the financial statements, so as to get a more in-depth information.